Financial Inclusion and Development in the CEMAC - Alter, Adrian; Yontcheva, Boriana (Washington, D.C. : International Monetary Fund, 2015)
This paper examines financial inclusion and development in the CEMAC. We explore the level of financial inclusion in the CEMAC through a benchmarking exercise.We construct a measure of financial development gap and analyze its determinants. Using panel data regressions, we find that inflation, income, and natural resources explain most of the financial development level but that better financial sector governance and stronger economic governance are positively associated with financial sector development. Richer and poorer countries can be equally far from their expected financial development levels. Finally, we use a benchmarking exercise to identify countries that have successfully reduced the financial development gap and propose policy measures that CEMAC countries could use to boost financial inclusion.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet